Effect of Photolithographic Biomimetic Surface Microstructure on Wettability and Droplet Evaporation Process - Zhihao Zhang; Yuying Yan (Biomimetics)
In nature, engineering technology and daily life, wetting phenomena are widespread and have essential roles and significance. Bionics is becoming increasingly important nowadays and exploring the mechanism that influences biomimetic surface microstructure on droplet wetting process and heat and mass transfer characteristics is becoming more meaningful. In this paper, based on photolithography technology, SU-8 photoresist was used as raw material to prepare biomimetic surfaces with microstructures in various arrangements. The research results show that the wettability of biomimetic functional surfaces can be regulated by regulating the shape and arrangement of photoresist micro-pillars. At the same time, the effects of surface microstructure configuration and roughness on the heat and mass transfer processes within the droplets were also comprehensively studied. The results show that a biomimetic surface with cylindrical micro-pillars can effectively inhibit the evaporative cooling effect of the liquid–vapour interface. This effect becomes more evident with the increase in roughness, and the interface temperature difference can be reduced by up to 18%. Similarly, the biomimetic surface with cylindrical micro-pillars can also effectively promote the evaporation rate of sessile droplets, which can be increased by about 13%. In addition, the research also shows that regardless of the structure, substrate temperature changes will significantly impact the wetting phenomenon of the biomimetic surface. This study aims to guide the optimal design of biomimetic surfaces prepared based on photoresistance.